Subcultural variability and protean-identification in gun culture. Issue 2 (4th March 2022) - Blithe, Sarah Jane; Lanterman, Jennifer L.
ABSTRACT: Gun culture in the Unites States is enmeshed in controversy, and is frequently described as a monolithic, static construct. In this paper, we argue that instead, gun culture is a fluid and fragmented collective of multiple subcultures that overlap, contradict, and coexist. Based on data collected through a collaborative event ethnography (CEE) at gun shows, we found that while gun collective members do strongly identify with gun culture, they also disidentify, schizo-identify, multi-identify, and change their identifications across multiple subcultures. In this way, people engage in protean identification, constantly changing arrays of organizational identifications. Ultimately, these contributions are useful for understanding stigmatized, hidden, or highly complex collectives and have practical implications for gun policy.